SPECKLE SUPPRESSION IN HANDHELD LASER PROJECTION DISPLAYS - Mohamed, Mahmoud (My University, 2020)
Micro-/pico-projectors are exciting technology as they represent a core enabling technology for the future growth of portable devices. They are currently involved in many fields such as automotive, defence & aerospace, healthcare, and media/entertainment. Solving the issue of speckle noise in such small projectors has been a challenge until now, as most of the effective techniques for speckle suppression are not suitable for such small sizes. The purpose of this dissertation is exploring and applying practical solutions for reducing the laser speckle noise for a handheld laser projector (micro-/pico-projectors). The first method is to introduce a laser source with low-level speckle noise. The source is designed based on end pumping of two cascaded laser crystals in the same cavity. The first crystal is Nd: YVO4 and the second is Nd: GdVO4 crystal. The output power ratio is adjusted mechanically to be 1:1. The output optical to optical efficiency is close to 50%. The output power at 1:1 power ratio has the lowest speckle noise level. The laser source is compact. Such a laser source is promising for micro-/pico-projectors. The second method is to reduce the laser speckle noise by a simple, low cost and compact optical method. Our novel method is to vibrate a lens with a small focal length in just one dimension (1D) in front of an optical diffuser. The method reduced the speckle noise by 81.25% and 75.6% for laser diode (LD) and diode-pumped solid-state (DPSS) laser sources, respectively. Finally, an optimisation was performed as follows: First, two laser sources are blended under specific conditions. Second, by adding another vibrating lens with a direction of vibration orthogonal to that of the first lens. Afterwards, the two optimisations are tested with a real pico-projector engine setup. The speckle contrast ratio was < 5%.